Pengaruh Media Sosial terhadap Minat Berkunjung Kembali Wisatawan Lokal di Masa Pandemi ke Daya Tarik Wisata Khusus Kintamani Bali - Ni Putu Ratna Sari (Jurnal Kajian Bali (Journal of Bali Studies), 2022)
Bali undoubtedly faces the most severe impacts from the COVID-19pandemic. As the new normal era comes, the Balinese starts visiting sometourist destinations. Social media postings about tourists’ visit enjoyingKintamani’s panorama have attracted other tourists to travel on the weekendor on the vacation. This research objective were to find out the role of socialmedia in promoting tourist attractions in Kintamani, Bangli regency, Bali;and to investigate impacts of social media to revisit Kintamani. This researchutilized quantitative approach of multiple regression analyses. Result of thisresearch showed that the social media were found to be effective in triggeringinterest of visitation during COVID-19 pandemic. In addition, easiness, trust,and information quality variables simultanously cause positive impacts andsignificantly (53.9%) impacts on interest to revisit Kintamani. This researchcontributed to the businessmen in utilizing social media to promote and selltheir tourism products during the pandemic era.